EDUCATION AND LANGUAGE: ENGLISH COMPETENCY IN PRIMARY SCHOOL STUDENTS IN THE INDUSTRIAL ERA 4.0 - Lubis, Namiroh; Nai'mah; Erni Munastiwi; Yozi Yulizah; Miswar (Darul Ilmi Bina Insan Foundation, 2024)
This research aims to analyze English language competency in the 4.0 era through education and learning. Data collection involved secondary data analysis through reduction and display. The findings indicate that English language competency in Indonesian elementary schools is a locally-content learning subject that enhances student skills by incorporating local wisdom as a resource for learning and development. English language skills are fostered to improve students' vocabulary, communication, and reading abilities, supporting both academic achievements and practical applications outside of education. The implementation of English language competence involves training students to enhance their communication skills in alignment with international knowledge standards. Overall, education and language serve as processes through which students develop soft skills and expand their knowledge base.